Kajian Peraturan Perundang-Undangan Tentang Pemberian Informasi Obat dan Obat Tradisonal di Indonesia - Supardi, Sudibyo; Handayani, Rini Sasanti; Herman, M. J.; Raharni, Raharni; Susyanty, Andi Leny (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2012)
Lack of information or inappopriate of information on medicine and traditional medicine caused unsuitable utilization of them. The objective of this study was analyzing the regulation of the medicine and traditional medicines information announcement and the implementation of the relevant institutions as well, even in the central, provincial and district level. Cross sectional study with qualitative approach due to the regulation of medicine and traditional medicine information announcement, as well as the related institutions. The study carried out at 2009, in Jakarta, Yogyakarta, Denpasar, Medan and Banjarmasin. The samples ofthis study were pharmacists as officers on The National Agency of Drug and Food Control (Badan POM), Provincial Health Offices, District Health Oﬂices, pharmaceutical companies, hospitals, pharmacies, and other relevant institutions. Data collecting has been conducted by depth interviews, focus group discussions, while the secondary data has been collected by multiplies of the document needed. Descriptive and qualitative analyzed the data, and final results completed by round table discussion. NADF C announce the information of medicine and traditional medicine to the community and pharmaceutical companies. Provincial Health Office and District Health Ojfice announce the information to the community by socialization, and announce directly to the patients in Primary Health Care, While the pharmaceutical companies provide their own products information. Besides, the hospitals and pharmacies provide the medicine information to the patients; Announcing the information to the community by the government has not been optimal yet to compensate traditional medicine advertizing, since the advertizing services to the community has not been used eﬂectively; The Indonesian Consumer Organization is one of the institution that participate in announcing information to the community. Besides, the pharmaceutical colleges and pharmacies has also provide information to the community.